Nutrient-stimulated glucagon-like peptide 1 release after body-weight loss and weight maintenance in human subjects - Adam, Tanja C. M; Lejeune, Manuela P. G. M.; Westerterp-Plantenga, Margriet S. (British journal of nutrition, 2006)
Glucagon-like peptide 1 (GLP-1) is a peptide hormone that is released in response to nutrient ingestion. Postprandial GLP-1 release has been reported to be attenuated in obese subjects, but reports on the effect of weight loss on GLP-1 are conflicting. The aim of the present study was to clarify the effect of a weight-loss period and a consecutive weight-maintenance period on nutrient-stimulated GLP-1 release in obese subjects. Nutrient-stimulated (standard breakfast; 1·9MJ) GLP-1 release was investigated in thirty-two obese subjects on three occasions: before weight loss (T1) (BMI 30·0 (sd 2·5) kg/m2); after a 6-week very-low-energy diet (VLED) (T2) (BMI 27·6 (sd 2·3) kg/m2); after a 3-month weight-maintenance period (T3) (BMI 27·9 (sd 2·3) kg/m2). At each occasion, following a fasting blood sample the test meal was fed and blood was drawn every 30min for 2h relative to ingestion in order to determine plasma GLP-1, insulin, glucose and NEFA concentrations. Subjects lost 7 (sd 3·4) kg during the VLED (P<0·0001) and regained 1 (sd 3·2) kg during the weight-maintenance period (NS). The area under the curve for nutrient-stimulated plasma GLP-1 (pmol/l×h) was significantly decreased (P=0·01) at T2 (6·8 (sd 1)) compared with T1 (12·8 (sd 2·9)) and T3 (11·1 (sd 1·5)). Since we found a rebound of concentrations after a weight-maintenance period, decrease after weight loss seems to be transient and possibly due to a negative energy balance.